2014
DOI: 10.2174/0929867321666131227161303
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Mediated Mitochondrial and Vascular Lesions as Markers in the Pathogenesis of Alzheimer Disease

Abstract: Mitochondrial dysfunction plausibly underlies the aging-associated brain degeneration. Mitochondria play a pivotal role in cellular bioenergetics and cell-survival. Oxidative stress consequent to chronic hypoperfusion induces mitochondrial damage, which is implicated as the primary cause of cerebrovascular accidents (CVA) mediated Alzheimer's disease (AD). The mitochondrial function deteriorates with aging, and the mitochondrial damage correlates with increased intracellular production of oxidants and pro-oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 153 publications
1
78
0
1
Order By: Relevance
“…Lipids and proteins in the inner mitochondrial membrane are highly susceptible to ROS, and lipid peroxidation has been observed in oxidative injury [187,195]. Damage to the inner membrane proteins and/or lipids can result in membrane depolarization and impaired mitochondrial function [82].…”
Section: Effects Of Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids and proteins in the inner mitochondrial membrane are highly susceptible to ROS, and lipid peroxidation has been observed in oxidative injury [187,195]. Damage to the inner membrane proteins and/or lipids can result in membrane depolarization and impaired mitochondrial function [82].…”
Section: Effects Of Oxidative Stressmentioning
confidence: 99%
“…In the AD brain, oxidative injury has been demonstrated in mitochondria of neuronal [82,187,196], and also in vascular (endothelial) and perivascular cells [72,89,197]. Cellular energy failure is demonstrated in the AD brain by post mortem studies showing deterioration of mitochondrial ultrastructure, formation of non-mature mitochondria ("hypoxic mitochondria" [72,89]) and excessive mtDNA deletions [72,195].…”
Section: Effects Of Oxidative Stressmentioning
confidence: 99%
“…Moreover, it has been shown that ROS is potentially toxic and may damage the proteins, lipids and nucleic acids of brain cells and mitochondria, including neurons and oligodendrocytes that may mediate toxicity. 88,89 Generation of ROS is controlled by sensitive genes called vitagenes. These genes encode proteins such as heat shock proteins, nutritional antioxidants which play a neuroprotective role.…”
Section: O X I D At I V E S T R E S Smentioning
confidence: 99%
“…Recent reviews claimed that accumulating evidence shows that the key factor in Alzheimer disease is oxidative stress (30,37).…”
Section: Oxidative Stressmentioning
confidence: 99%